Shores in the city: opportunities, threaths and challenges : viewpoints of citizens in Helsinki. - Lodenius, Martin (Boreal Environment Research, 2005)
The attitudes of citizens in Helsinki towards sea shores were investigated by means of three different surveys in the late summer of 2002. Survey data showed clear evidence that the shores are important to the citizens of Helsinki. People visited the shores often and participated in many different activities including general recreation, sunbathing, nature observation, swimming and physical exercise. Problems mentioned in the surveys were related on the other hand to the purity and tidiness of the water and the shores and on the other hand to the development plans of the growing city. Most people want to keep the shores in natural condition, but at the same time they also ask for services like litter bins, benches and toilets. People using boats would appreciate better garbage management, fire places and landing stages. There was some variation among different age groups and areas, but generally the citizens of Helsinki are quite unanimous in their opinions concerning the importance of shores and archipelago for physical and mental welfare.